Effects of Self-focused Augmented Reality on Health Perceptions During the COVID-19 Pandemic: A Web-Based Between-Subject Experiment - Ayanna Seals; Monsurat Olaosebikan; Jennifer Otiono; Orit Shaer; Oded Nov (JMIR Publications, 2021)
BackgroundSelf-focused augmented reality (AR) technologies are growing in popularity and present an opportunity to address health communication and behavior change challenges. ObjectiveWe aimed to examine the impact of self-focused AR and vicarious reinforcement on psychological predictors of behavior change during the COVID-19 pandemic. In addition, our study included measures of fear and message minimization to assess potential adverse reactions to the design interventions. MethodsA between-subjects web-based experiment was conducted to compare the health perceptions of participants in self-focused AR and vicarious reinforcement design conditions to those in a control condition. Participants were randomly assigned to the control group or to an intervention condition (ie, self-focused AR, reinforcement, self-focus AR × reinforcement, and avatar). ResultsA total of 335 participants were included in the analysis. We found that participants who experienced self-focused AR and vicarious reinforcement scored higher in perceived threat severity (P=.03) and susceptibility (P=.01) when compared to the control. A significant indirect effect of self-focused AR and vicarious reinforcement on intention was found with perceived threat severity as a mediator (b=.06, 95% CI 0.02-0.12, SE .02). Self-focused AR and vicarious reinforcement did not result in higher levels of fear (P=.32) or message minimization (P=.42) when compared to the control. ConclusionsAugmenting one's reflection with vicarious reinforcement may be an effective strategy for health communication designers. While our study's results did not show adverse effects in regard to fear and message minimization, utilization of self-focused AR as a health communication strategy should be done with care due to the possible adverse effects of heightened levels of fear.